2018
DOI: 10.1007/s00431-018-3227-6
|View full text |Cite
|
Sign up to set email alerts
|

Sweating ability of patients with p63-associated syndromes

Abstract: Sweating deficiency has been reported to represent a cardinal symptom of ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome and ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome, two rare p63-associated disorders. According to online resources, hypohidrosis may lead to most life-threatening complications in affected patients. Thus, counseling on the prevention of hyperthermia would be indispensable in case of such syndromes, although detailed information on this issue is missing in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Most affected patients have nail dystrophy and dental abnormalities, including hypodontia and conical teeth [ 10 , 11 ]. Sweating may be decreased, with resultant thermal intolerance [ 12 ]. Cleft palate with or without cleft lip occurs in all AEC syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most affected patients have nail dystrophy and dental abnormalities, including hypodontia and conical teeth [ 10 , 11 ]. Sweating may be decreased, with resultant thermal intolerance [ 12 ]. Cleft palate with or without cleft lip occurs in all AEC syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hay-Wells or AEC syndrome is an autosomal dominant genetic disease characterized the presence of ankyloblepharon, ectodermal abnormalities (including sparse and frizzy hair, skin defects, nail alterations, dental changes, and hypohidrosis) associated with a clefting of the lip and/ or the palate. The majority of authors consider these as the cardinal features suggestive of this syndrome [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. It has been reported that AEC syndrome includes erythroderma at birth with desquamation, superficial erosion and crusting [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic features include split hand/foot deformity (ectrodactyly),[ 50 ] light-colored hair that is sparse, coarse, and dry, sparse eyebrows and eyelashes, thin, brittle nails, xerosis with variable sweating[ 51 ] and cleft lip/palate [ Figure 4 ]. Other features include dental anomalies, midface hypoplasia, syndactyly, oligodactyly, absent lacrimal puncta (leading to keratitis, blepharitis, dacrocystitis, corneal ulcers), genitourinary anomalies[ 52 ] and endocrine abnormalities.…”
Section: (C) Disorders Of the Tp63 Pathwaymentioning
confidence: 99%